2014
DOI: 10.1002/pon.3656
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing live and telemedicine deliveries of an imagery‐based behavioral intervention for breast cancer survivors: reducing symptoms and barriers to care

Abstract: Objective This multi-site randomized trial evaluates the quality of life (QOL) benefits of an imagery-based group intervention titled “Envision the Rhythms of Life” (ERL). Methods Breast cancer survivors >6 weeks post-treatment were randomized to attend five weekly 4-hour group sessions at a community center with therapist present (live-delivery; LD, n=48); therapist streamed via telemedicine (telemedicine-delivery; TD, n=23); or to a waitlist control group (WL, n=47). Weekly individual phone calls to encour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
163
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(165 citation statements)
references
References 35 publications
0
163
0
2
Order By: Relevance
“…The eHealth interventions used in the eligible studies were albeit heterogeneous and diverse in type and content. eHealth interventions adopted in the eligible studies included educational programs and behavior change interventions, including psycho‐educational modules on fatigue, anxiety, depression, diet, exercise, sleep, and social relationships, mindfulness‐based cognitive therapy, and an imagery‐based behavioral intervention . Two studies investigated a web‐based exercise intervention …”
Section: Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The eHealth interventions used in the eligible studies were albeit heterogeneous and diverse in type and content. eHealth interventions adopted in the eligible studies included educational programs and behavior change interventions, including psycho‐educational modules on fatigue, anxiety, depression, diet, exercise, sleep, and social relationships, mindfulness‐based cognitive therapy, and an imagery‐based behavioral intervention . Two studies investigated a web‐based exercise intervention …”
Section: Systematic Reviewmentioning
confidence: 99%
“…A range of different outcome measures was used. In 6 studies (67%), a significant reduction in fatigue was reported for the intervention group relative to the comparison group after 9 weeks (CIS: P < 0.01); MFSI‐SF: P ≤ 0.001), after 12 weeks (BFI: P < 0.01); (BFI: P ≤ 0.001; FSS: P ≤ 0.001) and after 6 months of follow‐up (R‐PFS: P < 0.01); (CIS‐fatigue severity: P < 0.05) …”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies testing interventions such as exercise (e.g., walking, Qigong), massage, and psychological strategies (e.g., guided imagery, virtual reality) have evaluated effects on overall symptom burden or symptom distress. 3540 Secondary effects of physical symptom interventions on related psychological outcomes are also common. For example, changes in anxiety, mood, and sleep have been evaluated as secondary effects of interventions to reduce hot flash severity.…”
Section: Evidence For Management Of Multiple Symptomsmentioning
confidence: 99%